Modified ardealite-based self-leveling mortar and preparation method thereof

By grinding and modifying the phosphogypsum treatment, modified phosphogypsum particles coated with calcium carbonate shells are formed, and combined with fluorine phosphorus adsorption particles, the problem of insufficient performance of phosphogypsum in self-leveling mortar is solved, and the structure of the mortar is significantly improved Strength and construction efficiency.

CN119390417APending Publication Date: 2025-02-07GUIZHOU JIEZHONGSEN BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411387801.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-07
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the application of phosphogypsum in self-leveling mortar is limited by problems such as insufficient performance, susceptibility to impurities, and slow hydration hardening speed, resulting in the structural strength of the self-leveling mortar not reaching the optimal level.

Method used

By grinding phosphogypsum to reduce the particle size, modifying phosphogypsum particles are formed, and the surface of it is coated with calcium carbonate shell. Fluorophosphorus adsorption particles are used to adsorb soluble impurities, improving the gelling performance and structural strength of the mortar.

Benefits of technology

The structural strength and construction efficiency of self-leveling mortar are significantly improved, the construction cycle is shortened, the construction cost is reduced, and the efficient utilization of phosphogypsum resources is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides modified ardealite-based self-leveling mortar and a preparation method thereof.The modified ardealite-based self-leveling mortar is prepared from modified ardealite particles, ardealite, cement, fluorine-phosphorus adsorption particles, a water reducing agent, a stabilizer and water.The preparation method of the modified ardealite-based self-leveling mortar comprises the steps that S1, the modified ardealite particles are prepared, S2, a chitosan microsphere intermediate is prepared, S3, the fluorine-phosphorus adsorption particles are prepared through the chitosan microsphere intermediate, and S4, the modified ardealite-based self-leveling mortar is prepared. S4, stirring the modified ardealite particles, ardealite, cement, fluorine-phosphorus adsorption particles and other components into homogenate, so as to obtain the modified ardealite-based self-leveling mortar; the modified ardealite-based self-leveling mortar prepared by compounding the raw materials such as the modified ardealite particles, the ardealite, the cement, the fluorine-phosphorus adsorption particles, the water reducing agent, the stabilizer and the water and optimizing the preparation process has self-leveling property and good structural strength, is simple, convenient and rapid to construct, can automatically level and can effectively improve the construction efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical industry, and in particular to a modified phosphogypsum-based self-leveling mortar and a preparation method thereof. Background Art

[0002] Phosphogypsum is a by-product of the phosphorus chemical industry. Its main component is calcium sulfate dihydrate. It is generally dark gray, blocky or granular, and has no obvious odor. With the development of the phosphorus chemical industry, the output of phosphogypsum has increased year by year, and its resource utilization has become an urgent problem to be solved. The large accumulation of phosphogypsum not only occupies land resources, but also may pollute the environment. Therefore, the conversion of phosphogypsum into high-value-added building materials, such as self-leveling mortar, through modification technology is an important way to realize the resource utilization of phosphogypsum. Self-leveling mortar relies on gravity and high fluidity to achieve the function of self-leveling. It is easy to construct and highly efficient. Compared with cement-based self-leveling mortar, gypsum-based self-leveling mortar has better volume stability and is not prone to cracking. At the same time, the hydration and hardening speed of gypsum-based self-leveling mortar is faster, which is conducive to shortening the construction period. The performance of original phosphogypsum is easily affected by impurities in the raw materials. It is acidic, has poor compatibility with admixtures, and has low strength. These defects limit the direct application of phosphogypsum in self-leveling mortar. Therefore, when using phosphogypsum to produce self-leveling mortar, the phosphogypsum needs to be modified. The performance of phosphogypsum, including strength, water resistance, compatibility with admixtures, etc., can be improved through modification technology so that it can meet the preparation requirements of self-leveling mortar.

[0003] Based on the above situation, in the prior art, the patent with publication number CN116693321B discloses a method for preparing a modified phosphogypsum-based self-leveling mortar, which relates to the technical field of building materials, including modified phosphogypsum powder, foaming particles, retarder and water. The foaming particles are mainly prepared by pressing the original phosphogypsum and sodium bicarbonate powder by a particle forming machine. The method for preparing the modified phosphogypsum-based self-leveling mortar can realize the low-cost and efficient resource utilization of phosphogypsum. The main component of the original phosphogypsum is calcium sulfate dihydrate. The present invention first converts the larger particles and block particles in the phosphogypsum into smaller particles by a grinder, and changes the particle size of the phosphogypsum to pave the way for the next step of rapid modification; since the ground phosphogypsum particles are small, the ground phosphogypsum can be dehydrated more quickly and efficiently in a box oven, so that the calcium sulfate dihydrate is converted into calcium sulfate hemihydrate and anhydrous calcium sulfate, and stronger gelling properties are obtained.

[0004] In the preparation process of the above-mentioned modified phosphogypsum-based self-leveling mortar, although the phosphogypsum is modified through drying, grinding, magnetic separation and other steps, there is no special removal or neutralization treatment for the common soluble impurities in the phosphogypsum, such as phosphates and fluoride ions. The presence of these impurities may affect the gelling properties of the modified phosphogypsum powder to a certain extent, and thus the structural strength of the finally prepared self-leveling mortar after solidification fails to reach the optimal level, and there is a potential disadvantage of insufficient strength. Summary of the invention

[0005] In view of the technical defects existing in the background technology, the present invention proposes a modified phosphogypsum-based self-leveling mortar and a preparation method thereof, which solves the above technical problems and meets the actual needs. The specific technical scheme is as follows: A modified phosphogypsum-based self-leveling mortar comprises the following ingredients in parts by weight: 100-150 parts of modified phosphogypsum particles, 40-50 parts of phosphogypsum, 10-20 parts of cement, 5-10 parts of fluorine-phosphorus adsorption particles, 0.1-5 parts of a water reducer, 0.1-5 parts of a stabilizer, and 30-60 parts of water. The modified phosphogypsum particles consist of a phosphogypsum particle inner core and a calcium carbonate shell layer coated on the outside of the phosphogypsum particle inner core, and the fluorine-phosphorus adsorption particles consist of carrier particles and a fluorine adsorbent and a phosphorus adsorbent loaded on the carrier particles.

[0006] Furthermore, the inner core of the phosphogypsum particles is formed by mixing the raw material phosphogypsum with a binder resin and then granulating the mixture. The binder resin is selected from one or more of acrylic resin, isocyanate resin or polyurethane resin.

[0007] Furthermore, the particle size of the inner core of the phosphogypsum particles is 0.5-1.0 mm, and the thickness of the calcium carbonate shell layer is 100-150 μm.

[0008] Furthermore, the particle size of the fluorine and phosphorus adsorption particles is 0.3-1.0 mm, the phosphorus adsorbent is selected from any one or more of hexyldimethyl glycidyl ammonium chloride, hexyldimethyl glycidyl ammonium chloride, and hexadecyldimethyl glycidyl ammonium chloride, and the fluorine adsorbent is composed of Fe 3+ Mg 2+ and Al 3+ The nitrate or chloride of the compound may be present alone or in admixture of several of these salts.

[0009] Furthermore, the water reducer is selected from any one of a polycarboxylic acid water reducer or a naphthalene water reducer, and the stabilizer is hydroxypropyl methylcellulose.

[0010] A method for preparing a modified phosphogypsum-based self-leveling mortar comprises the following steps: S1. Mixing the raw material phosphogypsum with the adhesive resin, placing them in a twin-screw extruder granulator for granulation to obtain phosphogypsum particles, dispersing the phosphogypsum particles in a sodium carbonate-methanol aqueous solution, heating and slowly dropping a calcium chloride solution under stirring to allow calcium carbonate to slowly grow on the surface of the phosphogypsum particles, continuing stirring and heating for a period of time, filtering, washing, placing the solid part in a tubular furnace, and calcining at 200° C. for 1-2 hours in a carbon dioxide-oxygen atmosphere to obtain modified phosphogypsum particles; S2. Dissolve ferric chloride, magnesium chloride and aluminum chloride in an acetic acid aqueous solution, then slowly add chitosan under stirring, stir until the solid is dissolved to obtain a mixed chitosan solution, use a syringe pump to drop the mixed chitosan solution into a sodium hydroxide solution to form chitosan microspheres, then continue stirring overnight, filter, wash the chitosan microspheres with deionized water until neutral, and dry to obtain a chitosan microsphere intermediate; S3. The chitosan microsphere intermediate is dispersed in a methanol solution, sodium hydroxide is added to adjust the pH to 8.5-10, heated, and then hexyldimethylglycidyl ammonium chloride is slowly added, and the reaction is continued for 6-7 hours, and then sodium hydroxide is continued to be used to adjust the pH to neutral, filtered, washed, and the solid is heated and dried to obtain fluorine phosphorus adsorption particles; S4. Evenly mix 150 parts of modified phosphogypsum particles, 50 parts of phosphogypsum, 10 parts of cement, 5 parts of fluorine phosphorus adsorption particles, 0.1 parts of water reducer, and 0.1 parts of stabilizer, then add 30 parts of water and stir into a homogenous slurry to obtain modified phosphogypsum-based self-leveling mortar.

[0011] Further, in step S1, the raw material phosphogypsum and the binding resin are stirred and mixed under heating conditions at 50°C, the mass ratio of the binding resin to the raw material phosphogypsum is 1:(30-50), the phosphogypsum particles are dispersed in a sodium carbonate-methanol aqueous solution, the mass percentage of each component in the sodium carbonate-methanol aqueous solution is: 5% sodium carbonate, 6% methanol, 89% water, the volume ratio of the phosphogypsum particles to the sodium carbonate-methanol aqueous solution is 1:5, the sodium carbonate-methanol aqueous solution is heated to 60°C, and 0.1% calcium chloride solution is slowly added dropwise under stirring to allow calcium carbonate to slowly grow on the surface of the phosphogypsum particles, stirring is continued and the reaction is carried out at a constant temperature for a period of time, filtering, washing, and the solid part is placed in a tubular furnace and calcined at 200°C for 1 hour in a gas atmosphere of 90% carbon dioxide-10% oxygen to obtain modified phosphogypsum particles.

[0012] Further, in step S2, 0.3 g of ferric chloride, 0.3 g of magnesium chloride, and 0.3 g of aluminum chloride are dissolved in 100 mL of 1% acetic acid aqueous solution, and then 1.5 g of chitosan is slowly added under stirring, and stirred until the solid is dissolved to obtain a mixed chitosan solution, and the mixed chitosan solution is dripped into a 1.5 mol / L sodium hydroxide solution using a syringe pump to form chitosan microspheres, and then continuously stirred overnight, filtered, and the chitosan microspheres are washed with deionized water to neutrality, and dried to obtain a chitosan microsphere intermediate.

[0013] Further, in step S3, the chitosan microsphere intermediate is dispersed in a 10% methanol solution, the volume ratio of the chitosan microsphere intermediate to the 10% methanol solution is 1:3, and then 1.0 mol / L sodium hydroxide is added to adjust the pH to 8.5-10, heated to 60°C, and then hexyldimethylglycidyl ammonium chloride is slowly added, and the reaction is continued for 6-7 hours, the mass ratio of the chitosan microsphere intermediate to hexyldimethylglycidyl ammonium chloride is 1:4, and then 1.0 mol / L sodium hydroxide is continued to be used to adjust the pH to neutral, filtered, washed, and the solid is heated and dried at 50°C to obtain fluorine phosphorus adsorption particles.

[0014] Furthermore, in step S4, the phosphogypsum needs to be dried before use at a temperature of 200° C. for 1 hour to convert the dihydrate calcium sulfate in the phosphogypsum into hemihydrate calcium sulfate and anhydrous calcium sulfate.

[0015] The beneficial effects of the present invention are: By preparing modified phosphogypsum particles and coating the inner core of the phosphogypsum particles with a calcium carbonate shell, the soluble phosphate and other impurities in the phosphogypsum are effectively sealed, and the overall hardness of the particles is enhanced, thereby improving the structural strength of the self-leveling mortar after solidification, making it more durable and stable, and introducing fluorine-phosphorus adsorption particles, which are composed of carrier particles and fluorine adsorbents and phosphorus adsorbents loaded thereon, can effectively adsorb soluble impurities such as phosphates and fluoride ions in the phosphogypsum, reduce the adverse effects of impurities on the performance of the self-leveling mortar, shorten the solidification time, and further improve the structural strength of the self-leveling mortar after solidification. By compounding raw materials such as modified phosphogypsum particles, phosphogypsum, cement, fluorine-phosphorus adsorption particles, water reducers, stabilizers and water, and optimizing the preparation process, the prepared modified phosphogypsum-based self-leveling mortar has self-leveling properties, is simple and quick to construct, can automatically level, and greatly improves the construction efficiency. At the same time, its faster solidification speed and good structural strength also shorten the construction period and reduce the construction cost. DETAILED DESCRIPTION

[0016] The implementation mode of the present invention is described below in conjunction with relevant embodiments. The implementation mode of the present invention is not limited to the following embodiments, and the present invention relates to relevant necessary components in the technical field, which should be regarded as the known technology in the technical field and can be known and mastered by the technical personnel in the technical field.

[0017] The invention discloses a modified phosphogypsum-based self-leveling mortar, comprising the following components in parts by weight: 100-150 parts of modified phosphogypsum particles, 40-50 parts of phosphogypsum, 10-20 parts of cement, 5-10 parts of fluorine-phosphorus adsorption particles, 0.1-5 parts of a water reducer, 0.1-5 parts of a stabilizer, and 30-60 parts of water. The modified phosphogypsum particles consist of a phosphogypsum particle inner core and a calcium carbonate shell layer coated on the outer surface of the phosphogypsum particle inner core, and the fluorine-phosphorus adsorption particles consist of carrier particles and a fluorine adsorbent and a phosphorus adsorbent loaded on the carrier particles.

[0018] The present invention forms a core of phosphogypsum particles by mixing phosphogypsum with an adhesive resin and coating the core with a layer of calcium carbonate shell, thereby effectively sealing impurities such as soluble phosphates in the phosphogypsum and preventing the adverse effects of these impurities in the self-leveling mortar. At the same time, the calcium carbonate shell enhances the overall hardness and stability of the particles, thereby improving the mechanical properties and durability of the self-leveling mortar. The fluorine-phosphorus adsorption particles are loaded with fluorine adsorbents and phosphorus adsorbents, and can quickly adsorb and fix harmful substances such as fluoride ions and phosphates in the phosphogypsum. The adsorption effect of the fluorine-phosphorus adsorption particles not only purifies the composition of the self-leveling mortar, but also promotes the solidification process of the self-leveling mortar, and improves the structural strength after solidification. In terms of composition, the self-leveling mortar of the present invention is compounded with modified phosphogypsum particles, phosphogypsum, cement and other components, and the components work synergistically, so that the self-leveling mortar can form a dense and stable structure during the solidification process. At the same time, the addition of fluorine-phosphorus adsorption particles, water reducers and stabilizers further improves the fluidity and working performance of the mortar, and improves the construction efficiency and quality.

[0019] The self-leveling mortar of the present invention makes full use of the industrial by-product phosphogypsum, and converts it into a high-value-added building material through modification, thereby realizing the resource utilization of waste. At the same time, the self-leveling mortar pays attention to both environmental protection and performance in the combination of ingredients, which not only reduces the emission of harmful substances, but also improves the mechanical properties and durability of the self-leveling mortar. Since the self-leveling mortar of the present invention has good structural strength, it can be used for leveling, repairing and decoration of indoor floors, and can also be used for hardening and waterproofing of outdoor floors.

[0020] As one of the preferred embodiments of the present invention, the inner core of the phosphogypsum particles is formed by granulating the raw material phosphogypsum and the binding resin after stirring and mixing, and the binding resin is selected from one or more of acrylic resin, isocyanate resin or polyurethane resin; the particle size of the inner core of the phosphogypsum particles is 0.5-1.0 mm, and the thickness of the calcium carbonate shell layer is 100-150 μm.

[0021] In the mixing and granulation process of the present invention, the addition of the adhesive resin improves the physical properties of the phosphogypsum particles, such as fluidity, compressive strength and water resistance, so that the particles are more suitable for the preparation of self-leveling mortar, etc. The close combination between the adhesive resin and the phosphogypsum particles forms a strong interface bonding force, which helps to improve the synergistic effect of the components in the mortar and enhance the overall performance. The adhesive resin of the present invention is preferably an acrylic resin. Specifically, the acrylic resin is a low molecular weight acrylic resin with a molecular weight of 5000. The low molecular weight acrylic resin has good fluidity and hydrophilicity. On the one hand, it is convenient to mix the raw material phosphogypsum and the acrylic resin. On the other hand, it makes the prepared phosphogypsum particle core have good hydrophilicity, which is beneficial to the calcium carbonate shell formation step. The acrylic resin has good adhesion and cohesion, and can effectively bond the raw material phosphogypsum particles tightly together to form a solid core structure, so that the core of the phosphogypsum particles can improve the mechanical properties of the overall mortar. At the same time, the acrylic resin is usually a low VOC (volatile organic compound) material, which is environmentally friendly and meets the requirements of modern building materials for environmental protection performance.

[0022] In the structure of the modified phosphogypsum particles, the particle size of the inner core of the phosphogypsum particles is preferably 1.0 mm, and the thickness of the calcium carbonate shell layer is 100 μm. Setting the particle size of the inner core of the phosphogypsum particles to 1.0 mm can provide sufficient filling effect and mechanical strength while ensuring good fluidity. A larger particle size helps to reduce the gaps between particles and improve the density and compressive strength of the mortar. At the same time, it makes it easier for the modified phosphogypsum particles to be evenly mixed with other ingredients such as cement and fluorophosphate adsorption particles during construction, thereby improving construction efficiency and quality. The calcium carbonate shell layer serves as a sealing layer for the inner core of the phosphogypsum particles, and its thickness is set to 100 μm, which can effectively resist external wear and tear, and maintain sufficient flexibility to adapt to the contraction and expansion of the mortar, thereby helping to improve the wear resistance and crack resistance of the mortar. The calcium carbonate shell layer helps to stabilize the structure of the inner core of the phosphogypsum particles, prevents them from breaking or falling off in the mortar system, thereby improving the stability and durability of the overall mortar.

[0023] As one of the preferred embodiments of the present invention, the particle size of the fluorine-phosphorus adsorption particles is 0.3-1.0 mm, the phosphorus adsorbent is selected from any one or more of hexyldimethyl glycidyl ammonium chloride, hexyldimethyl glycidyl ammonium chloride, and hexadecyldimethyl glycidyl ammonium chloride, and the fluorine adsorbent is composed of Fe3+ Mg 2+ and Al 3+ The nitrate or chloride of the compound may be present alone or in admixture of several of these salts.

[0024] The fluorine-phosphorus adsorption particles of the present invention achieve effective adsorption of soluble phosphates and fluoride ions by loading fluorine adsorbents and phosphorus adsorbents with specific adsorption characteristics and utilizing mechanisms such as electrostatic adsorption, chemical adsorption and ion exchange. This process not only helps to purify harmful substances in the mortar system, but also improves the mechanical properties and durability of the mortar.

[0025] The particle size of the fluorine-phosphorus adsorption particles is preferably 1.0 mm, the phosphorus adsorbent is preferably hexyldimethylglycidyl ammonium chloride, the fluorine adsorbent is preferably an equal mass mixture of three chlorides: ferric chloride, magnesium chloride, and aluminum chloride. Hexyldimethylglycidyl ammonium chloride has lipophilic groups and hydrophilic groups, and can electrostatically interact with phosphate ions in an aqueous solution or form chemical bonds, thereby adsorbing them from the solution to the surface of the fluorine-phosphorus adsorption particles. The fluorine adsorbent contains Fe³⁺, Mg²⁺ and Al³⁺. These metal ions are easily hydrolyzed in water to form positively charged hydroxide colloids, have a strong affinity for fluoride ions, and can adsorb fluoride ions onto particles through coordination or ion exchange.

[0026] When phosphate ions or fluoride ions in the solution approach the adsorption particles, due to the charge characteristics of the adsorbent surface, such as the positive charge of quaternary ammonium salts or the positive charge of metal hydroxides, these ions will be electrostatically attracted and attached to the surface of the fluoride-phosphorus adsorption particles. In addition to the electrostatic effect, the fluoride-phosphorus adsorption particles can also react chemically with phosphate ions or fluoride ions to form more stable chemical bonds. For example, metal ions such as Fe³⁺, Mg²⁺ and Al³⁺ can form coordination bonds with fluoride ions, or form precipitates with phosphate ions.

[0027] As one of the preferred embodiments of the present invention, the water reducer is selected from any one of polycarboxylic acid water reducer or naphthalene water reducer, and the stabilizer is hydroxypropyl methylcellulose.

[0028] The water reducer of the present invention is preferably a polycarboxylate water reducer. The polycarboxylate water reducer has an extremely high water reduction rate and can effectively reduce the water consumption of the self-leveling mortar, thereby improving the strength and durability of the modified self-leveling mortar. This is because the hydrophilic groups in the molecular structure of the polycarboxylate water reducer can be adsorbed on the surface of cement, phosphogypsum, and modified phosphogypsum particles to form a lubricating film, which reduces the friction and cohesion between cement, phosphogypsum, and modified phosphogypsum particles and other materials, making the prepared modified phosphogypsum self-leveling mixed system easier to mix, thereby improving the fluidity of the self-leveling mortar. In addition to the water-reducing effect, the polycarboxylate water reducer can also improve the compressive strength and flexural strength of the self-leveling mortar to a certain extent, because the use of the water reducer reduces the water consumption, so that the self-leveling mortar can form a denser structure during the hardening process, thereby improving its mechanical properties.

[0029] As a stabilizer with good performance, hydroxypropyl methylcellulose can effectively improve the water retention and workability of self-leveling mortar. Hydroxypropyl methylcellulose can form a continuous network structure in the self-leveling mortar to prevent water from evaporating too quickly, thereby maintaining the humidity and fluidity of the self-leveling mortar, making the construction smoother. At the same time, hydroxypropyl methylcellulose can also enhance the adhesion between the self-leveling mortar and the base layer. The functional groups such as hydroxyl and methoxy in the molecular structure of hydroxypropyl methylcellulose can chemically react or physically adsorb with materials such as cement to form a strong bonding point, reducing the occurrence of hollowing and falling off. In addition, hydroxypropyl methylcellulose can also adjust the consistency of self-leveling mortar and prolong the operating time, so that construction personnel have more time for leveling and finishing work.

[0030] The invention discloses a method for preparing a modified phosphogypsum-based self-leveling mortar, comprising the following steps: S1. Mixing the raw material phosphogypsum with the adhesive resin, placing them in a twin-screw extruder granulator for granulation to obtain phosphogypsum particles, dispersing the phosphogypsum particles in a sodium carbonate-methanol aqueous solution, heating and slowly dropping a calcium chloride solution under stirring to allow calcium carbonate to slowly grow on the surface of the phosphogypsum particles, continuing stirring and heating for a period of time, filtering, washing, placing the solid part in a tubular furnace, and calcining at 200° C. for 1-2 hours in a carbon dioxide-oxygen atmosphere to obtain modified phosphogypsum particles; S2. Dissolve ferric chloride, magnesium chloride and aluminum chloride in an acetic acid aqueous solution, then slowly add chitosan under stirring, stir until the solid is dissolved to obtain a mixed chitosan solution, use a syringe pump to drop the mixed chitosan solution into a sodium hydroxide solution to form chitosan microspheres, then continue stirring overnight, filter, wash the chitosan microspheres with deionized water until neutral, and dry to obtain a chitosan microsphere intermediate; S3. The chitosan microsphere intermediate is dispersed in a methanol solution, sodium hydroxide is added to adjust the pH to 8.5-10, heated, and then hexyldimethylglycidyl ammonium chloride is slowly added, and the reaction is continued for 6-7 hours, and then sodium hydroxide is continued to be used to adjust the pH to neutral, filtered, washed, and the solid is heated and dried to obtain fluorine phosphorus adsorption particles; S4. Evenly mix 50 parts of modified phosphogypsum particles, 50 parts of phosphogypsum, 10 parts of cement, 5 parts of fluorine phosphorus adsorption particles, 0.1 parts of water reducer, and 0.1 parts of stabilizer, then add 30 parts of water and stir into a homogenous slurry to obtain modified phosphogypsum-based self-leveling mortar.

[0031] The method of the present invention makes full use of the industrial waste material phosphogypsum, and converts it into high-performance self-leveling mortar through modification and compounding, which not only solves the problem of handling phosphogypsum, but also realizes the effective utilization of resources; the present invention uses a twin-screw extrusion granulator to mix phosphogypsum and a bonding resin to form granules, and then reacts a sodium carbonate-methanol aqueous solution with calcium chloride to make calcium carbonate grow on the surface of phosphogypsum particles to form a stable shell layer, thereby improving the surface properties of the phosphogypsum particles and enhancing their mechanical properties and durability. The formation of the calcium carbonate shell layer improves the hardness and compressive strength of the modified phosphogypsum particles, so that the performance of the final self-leveling mortar can be the same To improve the performance of the self-leveling mortar, the fluorine-phosphorus adsorption particles are formed by introducing metal ions such as Fe³⁺, Mg²⁺ and Al³⁺ into the chitosan microspheres, and then introducing hexyldimethylglycidyl ammonium chloride on their surface to form particles with fluorine-phosphorus adsorption capacity. The fluorine-phosphorus adsorption particles can effectively adsorb and fix harmful substances such as fluoride and phosphate in the mortar, thereby improving the environmental friendliness of the self-leveling mortar and the structural strength after solidification. At the same time, before using the phosphogypsum, the dihydrate calcium sulfate in it is converted into hemihydrate calcium sulfate and anhydrous calcium sulfate through high-temperature drying. This conversion is beneficial to improving the activity of the phosphogypsum, so that the self-leveling mortar obtains stronger gelling properties, thereby increasing the structural strength of the self-leveling mortar after solidification.

[0032] As one of the preferred embodiments of the present invention, in step S1, the raw material phosphogypsum and the binding resin are stirred and mixed under heating conditions at 50°C, the mass ratio of the binding resin to the raw material phosphogypsum is 1:(30-50), the phosphogypsum particles are dispersed in a sodium carbonate-methanol aqueous solution, the mass percentage of each component in the sodium carbonate-methanol aqueous solution is: 5% sodium carbonate, 6% methanol, 89% water, the volume ratio of the phosphogypsum particles to the sodium carbonate-methanol aqueous solution is 1:5, the sodium carbonate-methanol aqueous solution is heated to 60°C, and 0.1% calcium chloride solution is slowly added dropwise under stirring to allow calcium carbonate to slowly grow on the surface of the phosphogypsum particles, stirring is continued and the reaction is carried out at a constant temperature for a period of time, filtering, washing, and the solid part is placed in a tubular furnace and burned at 200°C for 1 hour in a gas atmosphere of 90% carbon dioxide-10% oxygen to obtain modified phosphogypsum particles.

[0033] The raw material phosphogypsum and the adhesive resin are stirred and mixed at a mass ratio of 30:1 under heating conditions of 50°C. The adhesive resin is an acrylic resin. The main function of the adhesive resin is to increase the bonding force between the phosphogypsum particles and improve its structural strength and performance. The mixed phosphogypsum particles are dispersed in a methanol aqueous solution containing sodium carbonate. Under heating and stirring conditions, calcium chloride solution is slowly added dropwise. The calcium ions ionized by calcium chloride in the solution react with carbonate ions to form a calcium carbonate colloidal system, so that calcium carbonate slowly grows on the surface of the particles to form a coating layer. The calcium carbonate shell can not only improve the surface properties of the phosphogypsum particles, but also improve their mechanical strength and durability.

[0034] After the above-mentioned chemical deposition process, the obtained phosphogypsum particles are filtered and washed to remove excess chemicals and impurities. Then, the solid part is placed in a tubular furnace and burned at 200°C for 1 hour in a specific gas atmosphere of 90% carbon dioxide-10% oxygen. The heat treatment process has two main functions: one is to further solidify the calcium carbonate shell on the surface of the phosphogypsum particles to make it more stable and dense. The dense calcium carbonate shell can seal the soluble phosphate and other impurities in the inner core of the phosphogypsum particles, and at the same time enhance the overall hardness of the modified phosphogypsum particles. The second is to improve its performance by changing the crystal structure inside the phosphogypsum. Burning in a gas atmosphere of 90% carbon dioxide-10% oxygen can inhibit the decomposition of the calcium carbonate shell. At the same time, during the burning process, the dihydrate calcium sulfate in the phosphogypsum is partially dehydrated and converted into hemihydrate calcium sulfate or anhydrous calcium sulfate.

[0035] As one of the preferred embodiments of the present invention, in step S2, 0.3 g of ferric chloride, 0.3 g of magnesium chloride, and 0.3 g of aluminum chloride are dissolved in 100 mL of 1% acetic acid aqueous solution, and then 1.5 g of chitosan is slowly added under stirring, and stirred until the solid is dissolved to obtain a mixed chitosan solution, and the mixed chitosan solution is dripped into a 1.5 mol / L sodium hydroxide solution using a syringe pump to form chitosan microspheres, and then continuously stirred overnight, filtered, and the chitosan microspheres are washed with deionized water to neutrality, and dried to obtain chitosan microsphere intermediates.

[0036] Chitosan is a natural high molecular weight polysaccharide with good biocompatibility and degradability. In acetic acid aqueous solution, the amino groups of chitosan are protonated, so that the charges on the chitosan molecular chain repel each other, thereby increasing its solubility in water. Therefore, in step S2, ferric chloride, magnesium chloride, and aluminum chloride are first dissolved in acetic acid aqueous solution to form an acidic solution containing metal ions, and then chitosan is slowly added under stirring. Chitosan dissolves in an acidic environment and forms a mixed chitosan solution with metal ions. When the mixed chitosan solution is dripped into a sodium hydroxide solution by an injection pump, the mixed chitosan solution is dripped into the sodium hydroxide solution in the form of droplets, and the chitosan droplets are rapidly cross-linked and solidified to form chitosan microspheres. The chitosan microspheres are kept in a dispersed state in the solution by continuous stirring, and gradually solidify as the reaction proceeds. After a period of stirring and solidification, the chitosan microspheres are separated from the solution by filtration, and then the microspheres are washed with deionized water to remove residual sodium hydroxide and other impurities until the microspheres are washed to neutrality. Finally, the washed chitosan microspheres are dried to obtain chitosan microsphere intermediates.

[0037] As one of the preferred embodiments of the present invention, in step S3, the chitosan microsphere intermediate is dispersed in a 10% methanol solution, the volume ratio of the chitosan microsphere intermediate to the 10% methanol solution is 1:3, and then 1.0 mol / L sodium hydroxide is added to adjust the pH to 8.5-10, heated to 60°C, and then hexyldimethylglycidyl ammonium chloride is slowly added, hexyldimethylglycidyl ammonium chloride and, the reaction is continued for 6-7 hours, the mass ratio of the chitosan microsphere intermediate to hexyldimethylglycidyl ammonium chloride is 1:4, and then 1.0 mol / L sodium hydroxide is continued to be used to adjust the pH to neutral, filtered, washed, and the solid is heated and dried at 50°C to obtain fluorine and phosphorus adsorption particles.

[0038] In step S3, the chitosan microsphere intermediate is dispersed in a 10% methanol solution, which is conducive to the good dispersion and subsequent reaction of the chitosan microsphere intermediate. Then, 1.0 mol / L sodium hydroxide was used to adjust the pH of the solution to 9. Under alkaline conditions, the amino and hydroxyl groups on the surface of the chitosan microsphere intermediate became more active. Hexyldimethyl glycidyl ammonium chloride was slowly added. Under alkaline conditions, the epoxy groups of hexyldimethyl glycidyl ammonium chloride could undergo a ring-opening reaction with the hydroxyl and amino groups on the surface of the chitosan microsphere to form a covalent bond, thereby grafting hexyldimethyl glycidyl ammonium chloride onto the surface of the chitosan microsphere. The positive charge on the surface of the chitosan microsphere was enhanced by the grafting reaction. The chitosan microsphere intermediate grafted with hexyldimethyl glycidyl ammonium chloride (i.e., fluorophosphorus adsorption particles) could adsorb negatively charged fluoride ions (F⁻) and phosphates (PO4³⁻, HPO4²⁻, H2PO4⁻) and other anions in phosphogypsum through electrostatic interactions. The quaternary ammonium salt groups on the surface of the fluorophosphorus adsorption particles carried a positive charge and could attract and capture negatively charged anions.

[0039] As one of the preferred embodiments of the present invention, in step S4, the phosphogypsum needs to be dried before use, and is dried at a temperature of 200° C. for 1 hour to convert the dihydrate calcium sulfate in the phosphogypsum into hemihydrate calcium sulfate and anhydrous calcium sulfate.

[0040] Step S4 is the treatment of the phosphogypsum in the formula of the self-leveling mortar, rather than the treatment of the raw material phosphogypsum in step S1. The phosphogypsum is mainly composed of calcium sulfate dihydrate, which contains a high amount of crystal water. During the drying process, as the temperature rises, the calcium sulfate dihydrate in the phosphogypsum will undergo a phase change, gradually losing part or all of the crystal water and turning into calcium sulfate hemihydrate or anhydrous calcium sulfate. The phosphogypsum after drying, especially the part turned into calcium sulfate hemihydrate and anhydrous calcium sulfate, has a tighter crystal structure, thereby improving the physical strength of the phosphogypsum. This can increase the structural strength of the self-leveling mortar after solidification when preparing the modified phosphogypsum-based self-leveling mortar later. The undried calcium sulfate dihydrate will reabsorb water after meeting water, which may cause volume expansion and affect the flatness and stability of the self-leveling mortar. After drying, the content of calcium sulfate dihydrate is reduced, the possibility of expansion is reduced, and the performance of the self-leveling mortar is more stable. In addition, through drying, the soluble impurities in the phosphogypsum, such as free phosphates, may be reduced or fixed to a certain extent, thereby reducing the adverse effects of these impurities on the performance of the self-leveling mortar and improving the overall utilization rate of the material.

[0041] Example 1

[0042] S1: The raw material phosphogypsum and acrylic resin are stirred and mixed at a mass ratio of 30:1 under heating conditions of 50°C, and the mixed materials are placed in a twin-screw extrusion granulator for granulation to obtain phosphogypsum particles, and the phosphogypsum particles are dispersed in a sodium carbonate-methanol aqueous solution (5% sodium carbonate, 6% methanol, 89% water), and the volume ratio of the phosphogypsum particles to the sodium carbonate-methanol aqueous solution is 1:5. The sodium carbonate-methanol aqueous solution is heated to 60°C, and 0.1% calcium chloride solution is slowly added dropwise under stirring, and the volume ratio of 0.1% calcium chloride solution to the sodium carbonate-methanol aqueous solution is 1:30. Stirring is continued and the reaction is carried out at a constant temperature for 7 hours, filtered, and washed to obtain phosphogypsum particles coated with calcium carbonate, and the coated phosphogypsum particles are placed in a tubular furnace, and calcined at 200°C for 1 hour in a gas atmosphere of 90% carbon dioxide-10% oxygen to obtain modified phosphogypsum particles.

[0043] S2: Dissolve 0.3 g of ferric chloride, 0.3 g of magnesium chloride, and 0.3 g of aluminum chloride in 100 mL of 1% acetic acid aqueous solution. Slowly add 1.5 g of chitosan while stirring, and stir until the solid is completely dissolved to obtain a mixed chitosan solution. Use a syringe pump to drop the mixed chitosan solution into a 1.5 mol / L sodium hydroxide solution to form chitosan microspheres. Continue stirring overnight, filter, wash the chitosan microspheres with deionized water until neutral, and dry to obtain chitosan microsphere intermediates.

[0044] S3: Disperse the chitosan microsphere intermediate in a 10% methanol solution at a volume ratio of 1:3, add 1.0 mol / L sodium hydroxide to adjust the pH to 9, heat to 60°C, slowly add hexyldimethylglycidyl ammonium chloride, the mass ratio of chitosan microsphere intermediate to hexyldimethylglycidyl ammonium chloride is 1:4, and continue to react for 6 hours. After the reaction is completed, continue to use 1.0 mol / L sodium hydroxide to adjust the pH to neutral, filter, wash, and heat and dry the solid at 50°C to obtain fluorine and phosphorus adsorption particles.

[0045] S4: 150 parts of modified phosphogypsum particles, 50 parts of phosphogypsum (dried at 200°C), 10 parts of cement, 5 parts of fluorophosphorus adsorption particles, 0.1 parts of polycarboxylic acid water reducer, and 0.1 parts of hydroxypropyl methylcellulose are mixed evenly, and then 30 parts of water are added, and the mixture is stirred into a uniform slurry using a mixer to form a self-leveling mortar.

[0046] Comparative Example 1 The difference between the comparative example and Example 1 is that when preparing the modified phosphogypsum particles in step S1, the calcium carbonate shell coating step is not performed, and an equal amount of phosphogypsum particles are used instead of the modified phosphogypsum particles. The remaining steps are the same as those in Example 1.

[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not perform the preparation of modified phosphogypsum particles in step S2, uses an equal amount of phosphogypsum instead of modified phosphogypsum particles, and the remaining steps are the same as Example 1.

[0048] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the preparation of fluorine-phosphorus adsorption particles in step S3 is not performed, and an equal amount of phosphogypsum is used to replace the fluorine-phosphorus adsorption particles. The remaining steps are the same as those in Example 1.

[0049] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the phosphogypsum used in step S4 of Comparative Example 4 is not dried at 200° C. for 1 h, and the remaining steps are the same as those of Example 1.

[0050] The modified phosphogypsum-based self-leveling mortars prepared in Example 1 and Comparative Examples 1-4 were tested for physical and mechanical properties according to the JC / T1023-2021 standard. The test results are shown in the following table.

[0051] By comparing Example 1 with Comparative Example 1, Example 1 is coated with a calcium carbonate shell in step S1. The results show that the 24h compressive strength and 28d absolute dry compressive strength of Example 1 are significantly higher than those of Comparative Example 1 (without calcium carbonate shell coating), which indicates that the calcium carbonate shell not only improves the hardness of the modified phosphogypsum particles, but also enhances its bonding with other components, thereby improving the compressive strength of the overall phosphogypsum self-leveling mortar. The calcium carbonate shell increases the surface hardness and density of the phosphogypsum particles, enabling them to better resist external forces. At the same time, it plays a bridging role in the hydration process of cement and phosphogypsum, thereby enhancing the interfacial bonding force.

[0052] Comparing Example 1 with Comparative Example 2, Example 1 uses modified phosphogypsum particles, and its various mechanical properties (such as flexural strength and compressive strength) are better than those of Comparative Example 2 (using phosphogypsum particles). This shows that the modified phosphogypsum particles have a higher mechanical strength through the combination of the core structure formed by the mixed granulation of the raw materials phosphogypsum and acrylic resin and the shell structure of calcium carbonate, thereby effectively improving the overall performance of the self-leveling mortar. At the same time, the modified phosphogypsum particles are dehydrated during the heat treatment process, which improves the core structure and performance of the modified phosphogypsum particles, further increases their own mechanical strength, and thus enhances the mechanical properties of the self-leveling mortar.

[0053] Comparison between Example 1 and Comparative Example 3 shows that the 28-day absolute dry flexural strength (18.2 MPa) of Example 1 (with fluorine-phosphorus adsorbing particles added) is significantly higher than that of Comparative Example 3 (without adding fluorine-phosphorus adsorbing particles, using an equal amount of phosphogypsum instead, with a value of 17.1 MPa). Similarly, the 24-hour compressive strength (23.1 MPa) is also higher than that of Comparative Example 3 (19.5MPa), which shows that the fluorine-phosphorus adsorption particles play a reinforcing role in the self-leveling mortar and improve the strength and stability of the self-leveling mortar. On the one hand, the fluorine-phosphorus adsorption particles themselves have a certain mechanical strength. Filling in the self-leveling mortar can increase the mechanical properties of the self-leveling mortar after solidification to a certain extent. On the other hand, the fluorine-phosphorus adsorption particles are loaded with fluorine adsorbents and phosphorus adsorbents with specific adsorption characteristics, and utilize mechanisms such as electrostatic adsorption, chemical adsorption and ion exchange to achieve effective adsorption of soluble phosphates and fluoride ions in the self-leveling mortar system. This process not only helps to purify harmful substances in the self-leveling mortar system, but also reduces the negative effects of soluble phosphates and fluoride ions on the performance of the self-leveling mortar, thereby improving the mechanical properties and durability of the self-leveling mortar.

[0054] In comparison between Example 1 and Comparative Example 4, the phosphogypsum raw material used in Example 1 was dried at 200°C for 1 hour, and the modified phosphogypsum-based self-leveling mortar prepared therefrom showed high values ​​in 24h flexural strength (11.5 MPa), 28d absolute dry flexural strength (18.2 MPa), 24h compressive strength (23.1 MPa) and 28d absolute dry compressive strength (39.6 MPa). In contrast, in Comparative Example 4, the phosphogypsum was not dried, and the strength values ​​of the self-leveling mortar prepared therefrom on the same test items were reduced, especially the 24h compressive strength and 28d absolute dry compressive strength decreased significantly, which shows that the phosphogypsum after drying can effectively increase the structural strength of the self-leveling mortar after solidification. Phosphogypsum is mainly composed of calcium sulfate dihydrate, which contains a high level of crystal water. During the drying process, as the temperature rises, the calcium sulfate dihydrate in the phosphogypsum will undergo a phase change, gradually losing part or all of the crystal water and turning into calcium sulfate hemihydrate and anhydrous calcium sulfate. The calcium sulfate hemihydrate and anhydrous calcium sulfate will undergo hydration during the stirring process of the self-leveling mortar, thereby giving the self-leveling mortar stronger gelling properties, thereby increasing the structural strength of the self-leveling mortar after solidification.

[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A modified phosphogypsum-based self-leveling mortar, characterized in that: The invention comprises the following ingredients in parts by weight: 100-150 parts of modified phosphogypsum particles, 40-50 parts of phosphogypsum, 10-20 parts of cement, 5-10 parts of fluorine-phosphorus adsorption particles, 0.1-5 parts of water reducer, 0.1-5 parts of stabilizer, and 30-60 parts of water. The modified phosphogypsum particles consist of a phosphogypsum particle inner core and a calcium carbonate shell layer coating the outer core of the phosphogypsum particle. The fluorine-phosphorus adsorption particles consist of carrier particles and a fluorine adsorbent and a phosphorus adsorbent loaded on the carrier particles.

2. The modified phosphogypsum-based self-leveling mortar according to claim 1, characterized in that: The inner core of the phosphogypsum particles is formed by mixing the raw material phosphogypsum with a binder resin and then granulating the mixture. The binder resin is selected from one or more of acrylic resin, isocyanate resin or polyurethane resin.

3. The modified phosphogypsum-based self-leveling mortar according to claim 1, characterized in that: The particle size of the inner core of the phosphogypsum particles is 0.5-1.0 mm, and the thickness of the calcium carbonate shell layer is 100-150 μm.

4. The modified phosphogypsum-based self-leveling mortar according to claim 1, characterized in that: The particle size of the fluorine and phosphorus adsorption particles is 0.3-1.0 mm, the phosphorus adsorbent is selected from any one or more of hexyldimethyl glycidyl ammonium chloride, hexyldimethyl glycidyl ammonium chloride, and hexadecyldimethyl glycidyl ammonium chloride, and the fluorine adsorbent is composed of Fe 3+ Mg 2+ and Al 3+ The nitrate or chloride of the compound may be present alone or in admixture of several of these salts.

5. The modified phosphogypsum-based self-leveling mortar according to claim 1, characterized in that: The water reducer is selected from any one of polycarboxylic acid water reducer or naphthalene water reducer, and the stabilizer is hydroxypropyl methylcellulose.

6. A method for preparing the modified phosphogypsum-based self-leveling mortar according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mixing the raw material phosphogypsum with the adhesive resin, placing them in a twin-screw extruder granulator for granulation to obtain phosphogypsum particles, dispersing the phosphogypsum particles in a sodium carbonate-methanol aqueous solution, heating and slowly dropping a calcium chloride solution under stirring to allow calcium carbonate to slowly grow on the surface of the phosphogypsum particles, continuing stirring and heating for a period of time, filtering, washing, placing the solid part in a tubular furnace, and calcining at 200° C. for 1-2 hours in a carbon dioxide-oxygen atmosphere to obtain modified phosphogypsum particles; S2. Dissolve ferric chloride, magnesium chloride and aluminum chloride in an acetic acid aqueous solution, then slowly add chitosan under stirring, stir until the solid is dissolved to obtain a mixed chitosan solution, use a syringe pump to drop the mixed chitosan solution into a sodium hydroxide solution to form chitosan microspheres, then continue stirring overnight, filter, wash the chitosan microspheres with deionized water until neutral, and dry to obtain a chitosan microsphere intermediate; S3. The chitosan microsphere intermediate is dispersed in a methanol solution, sodium hydroxide is added to adjust the pH to 8.5-10, heated, and then hexyldimethylglycidyl ammonium chloride is slowly added, and the reaction is continued for 6-7 hours, and then sodium hydroxide is continued to be used to adjust the pH to neutral, filtered, washed, and the solid is heated and dried to obtain fluorine phosphorus adsorption particles; S4. Evenly mix 150 parts of modified phosphogypsum particles, 50 parts of phosphogypsum, 10 parts of cement, 5 parts of fluorine phosphorus adsorption particles, 0.1 parts of water reducer, and 0.1 parts of stabilizer, then add 30 parts of water and stir into a homogenous slurry to obtain modified phosphogypsum-based self-leveling mortar.

7. The method for preparing the modified phosphogypsum-based self-leveling mortar according to claim 6, characterized in that: In step S1, the raw material phosphogypsum and the binding resin are stirred and mixed under heating conditions at 50° C., the mass ratio of the binding resin to the raw material phosphogypsum is 1:(30-50), the phosphogypsum particles are dispersed in a sodium carbonate-methanol aqueous solution, the mass percentage of each component in the sodium carbonate-methanol aqueous solution is: 5% sodium carbonate, 6% methanol, 89% water, the volume ratio of the phosphogypsum particles to the sodium carbonate-methanol aqueous solution is 1:5, the sodium carbonate-methanol aqueous solution is heated to 60° C., and 0.1% calcium chloride solution is slowly added dropwise under stirring to allow calcium carbonate to slowly grow on the surface of the phosphogypsum particles, stirring is continued and the reaction is carried out at a constant temperature for a period of time, the reaction is filtered, and the solid part is placed in a tubular furnace and calcined at 200° C. for 1 hour in a gas atmosphere of 90% carbon dioxide-10% oxygen to obtain modified phosphogypsum particles.

8. The method for preparing the modified phosphogypsum-based self-leveling mortar according to claim 6, characterized in that: In step S2, 0.3 g of ferric chloride, 0.3 g of magnesium chloride, and 0.3 g of aluminum chloride are dissolved in 100 mL of 1% acetic acid aqueous solution, and then 1.5 g of chitosan is slowly added under stirring, and stirred until the solid is dissolved to obtain a mixed chitosan solution. The mixed chitosan solution is dripped into a 1.5 mol / L sodium hydroxide solution using a syringe pump to form chitosan microspheres, and then continuously stirred overnight, filtered, and the chitosan microspheres are washed with deionized water to neutrality, and dried to obtain a chitosan microsphere intermediate.

9. The method for preparing the modified phosphogypsum-based self-leveling mortar according to claim 6, characterized in that: In step S3, the chitosan microsphere intermediate is dispersed in a 10% methanol solution, the volume ratio of the chitosan microsphere intermediate to the 10% methanol solution is 1:3, and then 1.0 mol / L sodium hydroxide is added to adjust the pH to 8.5-10, heated to 60°C, and then hexyldimethylglycidyl ammonium chloride is slowly added, and the reaction is continued for 6-7 hours. The mass ratio of the chitosan microsphere intermediate to hexyldimethylglycidyl ammonium chloride is 1:4, and then 1.0 mol / L sodium hydroxide is continued to be used to adjust the pH to neutral, filtered, washed, and the solid is heated and dried at 50°C to obtain fluorine and phosphorus adsorption particles.

10. The method for preparing the modified phosphogypsum-based self-leveling mortar according to claim 6, characterized in that: In step S4, the phosphogypsum needs to be dried before use at a temperature of 200° C. for 1 hour to convert the dihydrate calcium sulfate in the phosphogypsum into hemihydrate calcium sulfate and anhydrous calcium sulfate.

Citation Information

Patent Citations

  • A method for preparing modified phosphogypsum-based self-leveling mortar

    CN116693321B